2013
DOI: 10.1002/pri.1550
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Strength, the Six-Minute Walk Test and Quality of Life in Chagas Cardiomyopathy

Abstract: The inspiratory muscle strength is reduced, and the decreased quality of life has a negative influence on the physical and emotional aspects of the patients with Chagas cardiomyopathy. No correlation was found between perceived exertion and the reduction of respiratory muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
2
22
2
1
Order By: Relevance
“…Of these, 10 were published in international journals, and 2 were published in Brazilian journals. Six cross-sectional studies evaluated HRQoL in ChD patients (Table 1) (5) (10) (14) (15) (16) (17) , two verifi ed the effect of non-surgical conservative treatments on HRQoL in Chagas dilated cardiomyopathy patients (Table 2) (18) (19) , and 4 correlated HRQoL with functional capacity in ChD patients (Table 3) (20) (21) (22) (23) . The studies found in our literature search showed heterogeneity in the patient samples: one article included patients presenting with all clinical forms of ChD (8.3%), two (16.7%) included patients with pacemakers, two (16.7%) did not mention the presence of cardiopathy, and 7 (58.3%) included patients with cardiopathy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 10 were published in international journals, and 2 were published in Brazilian journals. Six cross-sectional studies evaluated HRQoL in ChD patients (Table 1) (5) (10) (14) (15) (16) (17) , two verifi ed the effect of non-surgical conservative treatments on HRQoL in Chagas dilated cardiomyopathy patients (Table 2) (18) (19) , and 4 correlated HRQoL with functional capacity in ChD patients (Table 3) (20) (21) (22) (23) . The studies found in our literature search showed heterogeneity in the patient samples: one article included patients presenting with all clinical forms of ChD (8.3%), two (16.7%) included patients with pacemakers, two (16.7%) did not mention the presence of cardiopathy, and 7 (58.3%) included patients with cardiopathy.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies indicated however that the presence of cardiac involvement in the disease seemed to have a negative effect on the patients' HRQoL. Vieira et al (23) compared the HRQoL between ChD patients with cardiopathy (n = 16, aged AQUAREL: assessment of quality of life and related events; ChD: Chagas disease; HRQoL: health-related quality of life; MLwHFQ: Minnesota living with heart failure questionnaire; PEDro: physiotherapy evidence database; SF-36: short-form of health survey; WHOQOL-BREF: WHO quality of life-BREF.…”
Section: Health-related Quality Of Life In Patients With Chagas Diseasementioning
confidence: 99%
“…The major findings of the present study were improvements in some physical-related QOL domains (physical functioning, role-physical, and bodily pain) and in the physical summary score of patients with Chagas heart failure after completing an 8-month cardiac rehabilitation program. These results are particularly important since studies have demonstrated that cardiac symptoms exert an important negative influence on QOL in patients with Chagas disease 13 . A previous analysis of the same dataset using a disease-specific questionnaire (Minnesota Living with Heart Failure) showed no overall improvement in health-related QOL, except among those with the greatest severity of cardiac impairment at baseline, reinforcing the deleterious impact of cardiac symptoms on health-related QOL 10 .…”
mentioning
confidence: 95%
“…All participants included in the study exhibited reduced respiratory muscle strength at baseline, as previously shown in patients with Chagas cardiomyopathy (36) (37) . Indeed, it is possible that any training stimulus, regardless of specificity to respiratory muscles, may improve respiratory muscle strength and decrease related symptoms, such as dyspnea and exercise intolerance (38) .…”
Section: Discussionmentioning
confidence: 70%